The Land-Field tidennūtu Transaction at Nuzi - Jordan, Gregory Doty (1986)
Ph.D. Dissertation; Hebrew Union College, Cincinnati, OH – Jewish Institute of Religion; Co-Referees: S. Greengus, S.Kaufman, Order No. DA8628297; cf. DissAbstr 47/10 (April 1987) 3848-A Präzisierung von 48:1188.